Aspects Of Immunopathology in Emergence and Development of Atherosclerosis: Review (Texas Journal of Medical Science, 2024)
The authors offer a review of the literature on various aspects of immunopathology in the occurrence and development of atherosclerosis, and provide information on a number of theories of the pathogenesis of atherosclerosis. Data is shown on both fundamental theories and current research of today.